Narrative review of social media as a research tool for diet and weight loss. (October 2020) - Hawks, Jessica R.; Madanat, Hala; Walsh-Buhi, Eric R.; Hartman, Sheri; Nara, Atsushi; Strong, David; Anderson, Cheryl
Abstract: This narrative review examined the following research questions: 1) What are the characteristics and outcomes of social media-based diet/weight loss studies to date? 2) What are the methodological characteristics of social media-based diet/weight loss studies? 3) What research strengths and limitations exist among social media-based diet/weight loss studies? We conducted a narrative review of studies related to diet, weight loss, and social media. Out of 37 included articles, most focused exclusively on Facebook (n = 13, 35%) or Twitter (n = 12, 32%). Of 20 studies (54%) analyzing social media content, most analyzed textual content (n = 13, 65%). About half of studies (n = 20, 54%) had no guiding theoretical framework, and about one-quarter used Social Cognitive Theory (SCT) (n = 10, 27%). Studies designs used were non-experimental (n = 15, 41%), experimental (n = 12, 32%), qualitative (n = 8, 22%), and mixed methods (n = 2, 5%). Intervention research thus far has consisted mostly of inadequately controlled and powered pilot studies. More rigorous randomized controlled trials should be conducted that build on data gathered from pilot research. Further research on how exposure to/interaction with diet/weight loss social media translates to individual behavior change will aid in addressing the US's obesity epidemic. Highlights: Diet for weight loss studies primarily use Twitter and Facebook. Majority of social media-based diet studies were non-experimental. More rigorous randomized controlled trials should be conducted to build on pilot data.